Tuberculosis and COVID-19 Co-infection: An Updated Review : Tuberculosis and COVID -19 Co-infection - Mishra, Ajay; George, Anu Anna; Sahu, Kamal Kant; Lal, Amos; Abraham, George (Acta Biomedica Atenei Parmensis, 2020)
Coronavirus disease (COVID 19) has involved millions of people all over the world. Tuberculosis (TB) continues to affect millions of people every year with high mortality. There is limited literature on the occurrence of COVID 19 in patients with TB. We reviewed the available data on various clinical details, management, and outcome among patients with COVID-19 and TB. 8 studies reported a total of 80 patients with this coinfection. These patients were reported from ten different countries, with Italy reporting the largest number of cases. Migrant, males constituted a major proportion of cases. Most reported patients were symptomatic. Fever, dry cough, and dyspnea were the most commonly reported symptoms. Bilateral ground glass opacities were more common in COVID 19 infection and cavitary lesions were more common in patients with TB. Most reported TB patients had been found to have mycobacterium tuberculosis from sputum culture in the background of pulmonary TB. Most patients of TB were treated with multidrug regimen antitubercular therapy. In all 8 studies, COVID 19 was treated as per the local protocol. Mortality was reported in more than 10% of patients. Mortality was higher in elderly patients (> 70 years) and amongst patient with multiple medical comorbidities